Streamlining Education System Through Waqf Enlargement - Imam Bahroni (At-Ta'dib, 2016)
This paper is aimed at discussing the development of education systembased on the Waqf Empowerment. It is an experience of Gontor ModernIntegrated Islamic Institution to maintain its existence through the activitiesof Waqf Enlargement. The spirit of self-reliance which has been implementedby Gontor through various economic enterprise activities inside the campus isthe total processes of educational activities, carried out by students andteachers themselves. They act as the subjects and objects of the education atthe same time. They teach themselves through various activities, creativitiesand social interaction for their character and personality building. Thislearning process is purposely undertaken in Gontor, because the basicprinciple of this system is to actualize the community orientation throughwhich the students in the campus guided and prepared to have a spirit ofself reliance. So when they back to the society to undertake the real life theyconfidently take their role to develop their society for the sake of Allah andunity of muslim ummah.